1976
DOI: 10.1136/jech.30.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of twin births from a climatic point of view.

Abstract: Epidemiology of twin births from a climatic point of view. The twinning rate was analysed using figures taken from statistics for Japan. During the years 1955 to 1959 there were 58 570 twin deliveries out of a total of 9 088 233, a frequency of 6-44 per 1000. Using Weinberg's differential method for zygosity estimation, the monozygotic twinning rate was 4 04 per 1000 and the dizygotic was 2-40. Twinning rates in 46 prefectures were also estimated and their correlations with meteorological parameters as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

1987
1987
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
1
15
1
Order By: Relevance
“…Elwood 6 noted that di zygoti c tw i nni ng rates i n Canadi an ci ti es (1952) show ed a seasonal vari ati on w i th an October maxi mum. Kami mura 7 reported for Japan that the bi rth rate of tw i ns rose to a maxi mum i n the l ate autumn or earl y w i nter, and Imai zumi et al 8 reported for Japan a hi gh preval ence of concepti ons of tw i ns i n April. James 9 identified a winter peak in triplet materni ti es that w as about 5% hi gher i n December than i n June i n Engl and and Wal es (1952-59 and 1963-75).…”
Section: Introductionmentioning
confidence: 99%
“…Elwood 6 noted that di zygoti c tw i nni ng rates i n Canadi an ci ti es (1952) show ed a seasonal vari ati on w i th an October maxi mum. Kami mura 7 reported for Japan that the bi rth rate of tw i ns rose to a maxi mum i n the l ate autumn or earl y w i nter, and Imai zumi et al 8 reported for Japan a hi gh preval ence of concepti ons of tw i ns i n April. James 9 identified a winter peak in triplet materni ti es that w as about 5% hi gher i n December than i n June i n Engl and and Wal es (1952-59 and 1963-75).…”
Section: Introductionmentioning
confidence: 99%
“…Seasonality of twinning has been reported from several countries [2][3][4][5][7][8][9][10][11]17]. However, the seasons when the excess of twinning was detected were not consistent among these reports which analysed the seasonality of overall twin births collectively for several years.…”
Section: Introductionmentioning
confidence: 99%
“…The similar trend has also been observed in the present study where differences in the seasonality of twin birth is seen between the periods 1984-89 and 1990-93. lnfact this seasonality may vary from year to year depending upon ever changing determinants. This attribute may explain the inconsistencies seen in various reports (James, 1976;Kamimura, 1976;Sharma, 1980Sharma, , 1995Richter et al, 1984;Nakamura et al 1987) as far as the seasons showing excess of twinning. Because all the countries may not share factors that cause seasonality of twin births.…”
Section: Seasonality Of Twinningmentioning
confidence: 72%
“…The other reported factors affecting twinning rates include geographic, marital status, social class and biology (Rushton, 1987). Secular and seasonal variations in ~wi~ning rates are also often reported (James, 1972(James, , 1976Kamimura, 1976;Brackenridge, 1977;Nielsen et al, 1978;Parisi and Caperna, 1981;lmaizumi, 1987).…”
Section: Introductionmentioning
confidence: 92%